Advertising Practices and Promotion in the Islamic World under the Shariah Observation:A Case Study on Bank Islam in Malaysia - Haque, Ahasanul; Ahmed, Khaliq; Jahan, Syeada Irfath (Indian Journal of Marketing, 2009)
This study is to identify and asses the existing advertising practices in the Islamic Bank under the shariah observation and also promotional strength which is needed to acquire by Islamic banks to compete with the conventional banking as well. Descriptive observation carried out to measure the gap and distance to reach in terms of promotional tool with the prominent conventional bank to Islamic bank. While Islamic institutions particularly the banks are in competitive advantaged compared to their rival that they are providing the banking procedure under the shariah observation. It is still needed to properly revise and adequately research to upgrade the real scenario under the light of Quran and sunnah. In case of product and special offerings of the Islamic banks, majority of customers who have the potentiality are in deep ignorance. Analyzing the most effective communication through promotion, this study also make the clear way to state the Islamic banking promotion on the right track. Such a way to make the business more profitable as well as acknowledged to the customer promotion is the most strongest tool for the business regardless product or services industry. Most latest advertising in Islamic institutions and its appropriate guideline under shariah observation needed to observe which resultant the concrete solution of lot of query inside the mind of the potential customer; who are still deciding up about the institution to which they would be loyal.